(untitled) (Oil and Gas Engineering, 2017)
Expediency of application of aluminium boring pipes is reasonable in oil and gas industry that assists the increase of reliability of boring column and reduction of refuses at well-drilling. Structural implementations of легкосплавних of boring pipes are generalized. Keywords: boring column, aluminum boring pipes, horizontal mining hole, horizontal mining hole of large length, reliability.